2017
DOI: 10.3390/ijerph14020123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gender on the Association of Urinary Phthalate Metabolites with Thyroid Hormones in Children: A Prospective Cohort Study in Taiwan

Abstract: Phthalates are considered endocrine disruptors. Our study assessed the gender-specific effects of phthalate exposure on thyroid function in children. In total, 189 Taiwanese children were enrolled in the study. One-spot urine and blood samples were collected for analyzing 12 phthalate metabolites in urine and thyroid hormones. The association between urinary phthalate metabolites and serum thyroid hormones was determined using a generalized linear model with a log link function; the children were categorized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 31 publications
1
22
1
Order By: Relevance
“…Influence of age or gender on phthalate metabolism has been described by Koch et al, detecting higher levels of oxidised metabolites in children than in adults [ 45 ]. Gender-specific changes in girls and boys have been reported regarding phthalate metabolites and thyroid hormones [ 46 ], and markers of peripubertal metabolic homeostasis [ 47 ], respectively. Slight differences were observed in our study between women and men, however, these were not statistically significant and, therefore, are not discussed further.…”
Section: Resultsmentioning
confidence: 99%
“…Influence of age or gender on phthalate metabolism has been described by Koch et al, detecting higher levels of oxidised metabolites in children than in adults [ 45 ]. Gender-specific changes in girls and boys have been reported regarding phthalate metabolites and thyroid hormones [ 46 ], and markers of peripubertal metabolic homeostasis [ 47 ], respectively. Slight differences were observed in our study between women and men, however, these were not statistically significant and, therefore, are not discussed further.…”
Section: Resultsmentioning
confidence: 99%
“…[ 39 ] Since 2016, research hotspots of BPA and thyroid hormones switched to “prenatal exposure” “pregnant women” and “children”. [ 40 , 41 ] The trend of BPA and thyroid hormones with the change in time was studied to preface some new orientations in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary phthalates are cross-sectionally associated with lower fT4 and higher TSH ( 99 , 113 , 114 ). One study has found an inverse association between non-DEHP and fT4 in girls only ( 113 ) and another study has reported inverse associations between DEHP concentrations and fT4 in girls ( 115 ). In the later, urinary concentrations of dibutyl phthalate have been inversely associated with fT3 in boys ( 115 ).…”
Section: Phthalatesmentioning
confidence: 99%
“…One study has found an inverse association between non-DEHP and fT4 in girls only ( 113 ) and another study has reported inverse associations between DEHP concentrations and fT4 in girls ( 115 ). In the later, urinary concentrations of dibutyl phthalate have been inversely associated with fT3 in boys ( 115 ). Higher concentrations of phthalates in maternal prenatal urine samples have been associated with lower thyroid hormones ( 116 ).…”
Section: Phthalatesmentioning
confidence: 99%